Transparent wood developed by introducing epoxy vitrimers into a delignified wood template. (3rd May 2021) - Wang, Kaili; Dong, Youming; Ling, Zhe; Liu, Xiaorong; Shi, Sheldon Q.; Li, Jianzhang
Abstract: Transparent wood (TW) has shown great potential in various functional applications, including light, thermal, electromagnetic, and energy management fields. Despite significant progress in functional TW, programmable shape-memory TW (PSMTW) has not yet been reported. Epoxy vitrimers with exchangeable dynamic covalent crosslinking networks exhibit excellent stimuli-responsive, shape-memory, reprocessing, and self-healing properties, which are suitable for fabricating smart TW. In this study, a TW with programmable shape-memory ability was developed by introducing transparent, refractive index-matching, and intelligent epoxy-based vitrimers into delignified wood. The transmittance and haze of the resultant TW with a thickness of 2 mm were approximately 60% and 95%, respectively. Vitrimers with dynamic covalent crosslinking networks perfectly combine the glass transition temperature ( Tg )-inducted phase change and topology freezing transition temperature ( Tv )-inducted rearrangement under thermal stimulus, which endow TW with excellent programmable shape-memory properties, such as shape-recovery, shape-programming, shape-erasing, and re-programming. The programmable shape-memory properties of TW have not been investigated thus far, and development of PSMTW would be a multi-functionalized and efficient application of TW-based materials. Graphical abstract: Image 1 Highlights: Programmable shape-memory transparent wood (PSMTW) was developed for the first time. Transmittance and haze of PSMTW with 2 mm thickness were about 60% and 95%. Programmable shape-memory was an unknown feature for the current transparent wood. PSMTW may create new possibilities toward the advanced and intelligent application.